Evaluation on methods in estimating the photovoltaic performances affected by module operation temperature in tropical region - Chand, M.R.R; Basrawi, Firdaus Firdaus; Abd Aziz, Azizuddin; Abdul Majid, Zafri Azran; Sulaiman, Shaharin Anwar; Zulkefli, Afzam (EDP Sciences, 2018)
This research work is intended to evaluate the reliability of commonly utilized empirical correlations of module operation temperature in estimating the photovoltaic performances in tropical region. The Nominal Operation Cell Temperature (NOCT) model, Tropical Field Operation Cell Temperature (tFOCT) model and the experimental back module temperature were selected for evaluation purposes. The models were evaluated by comparing the performance characteristics of a 250W monocrystalline photovoltaic module installed at University Malaysia Pahang. The monocrystalline back module temperature and power output as well as the environmental data including both solar irradiation and ambient temperature were monitored to assist the analysis. Based on the 5 consecutive day experimental data, results indicated that the module operation temperature estimated by tFOCT model had the closest value to the experimental back module temperature. Whereas, the temperature estimated by NOCT model showed the highest deviation up to 25.8% from the experimental back module temperature. However, in terms of estimating the photovoltaic module power output, the NOCT model had the closest value to the experimentally measured power output. The results also indicated that utilizing the back module temperature often mislead the estimation of photovoltaic module power output. In addition, the deviation of estimated power output from NOCT model, tFOCT model and back module operation temperature as compared to the experimental power output were 15.4%, 18.87% and 21.2%, respectively. Thus, the NOCT model demonstrated better estimation of power output as compared to the experimental result than tFOCT model, and back module temperature. However, better estimation method for tropical regions is still needed because three methods evaluated in this study shows deviation of more than 15.4% from the measured power output.